2017
DOI: 10.1051/sicotj/2016039
|View full text |Cite
|
Sign up to set email alerts
|

Morphological classification of acromial spur: correlation between Rockwood tilt view and arthroscopic finding

Abstract: Purpose and hypothesis: Acromion spur is the extrinsic factor for impingement syndrome and rotator cuff tear. The Rockwood tilt view can be used to evaluate prominence of the anterior acromion, however no study has shown the correlation of findings between the Rockwood tilt view and the arthroscopic finding. Methods: We developed the arthroscopic classification of acromion spur as type 1 flat spur, type 2 bump spur, type 3 heel spur, type 4 keel spur, and type 5 irregular spur. Patients with rotator cuff syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A subsequent study using conventional radiographs reported a relationship between the shape of the acromion and the presence of rotator cuff disease. 7,20,21 Although these studies confirmed an association between rotator cuff disease and acromial shape, a causal relationship between the shape of the acromion and rotator cuff disease was not established. 21,22 The arthroscopic procedure didn't take much time, although this study report a series at the beginning of the experience.…”
Section: Discussionmentioning
confidence: 96%
“…A subsequent study using conventional radiographs reported a relationship between the shape of the acromion and the presence of rotator cuff disease. 7,20,21 Although these studies confirmed an association between rotator cuff disease and acromial shape, a causal relationship between the shape of the acromion and rotator cuff disease was not established. 21,22 The arthroscopic procedure didn't take much time, although this study report a series at the beginning of the experience.…”
Section: Discussionmentioning
confidence: 96%
“…The AHD has been widely used as a parameter to represent the rotator cuff integrity [1]. The AHD has been measured commonly by the conventional radiograph [15][16][17] despite the likelihood of misinterpretation due to the need for a specific position. For this reason, the use of MRI has been described to overcome the limitation of the conventional radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The heel spur was the most common type in their rotator cuff tear group; the mean acromial thickness in their cohort was 8.0 mm, but was thicker in the rotator cuff tear group. Kongmalai et al [ 20 ] classified acromial spurs based on 30° caudal-tilt view and arthroscopic findings, where keel spur was the most common finding, followed by heel spur. These authors [ 20 ] described patients with either of these spur types as “being at-risk” of a supraspinatus tendon tear.…”
Section: Discussionmentioning
confidence: 99%
“…Kongmalai et al [ 20 ] classified acromial spurs based on 30° caudal-tilt view and arthroscopic findings, where keel spur was the most common finding, followed by heel spur. These authors [ 20 ] described patients with either of these spur types as “being at-risk” of a supraspinatus tendon tear. In our study, laterally protruding or medial-type spurs on the short axis of the subscapularis or long axis of the long head of the biceps were not analyzed by ultrasonography.…”
Section: Discussionmentioning
confidence: 99%